What Drives Retail Investors' Decisions in the Indonesian Market? Understanding the Role of Cognitive and Social Biases - Aufaa Hasbul Qahhar Adhytya; Abdur Rafik (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2026)
Purpose: This study examines the effects of representativeness bias, availability bias, and herding behavior on retail investors' investment decisions in Indonesia. It also investigates whether internal locus of control moderates the relationship between behavioral biases and investment decisions.Method: A quantitative survey approach was employed using data from 302 active retail investors in the Indonesian capital market, selected through purposive sampling. Data were collected using a structured questionnaire with a five-point Likert scale and analyzed using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) technique.Result: The results indicate that representativeness bias, availability bias, and herding behavior have positive and significant effects on retail investors' investment decisions, suggesting that decisions are largely driven by heuristic judgments and social influence rather than purely rational evaluation. However, internal locus of control does not significantly moderate the relationships between behavioral biases and investment decisions, suggesting that individual psychological control does not automatically function as a debiasing mechanism in highly digitalized and socially influenced investment environments.Practical Implications for Economic Growth and Development: The results highlight the importance of behavioral-based financial education that emphasizes bias awareness to improve decision-making quality, promote more efficient capital allocation, and enhance capital market stability.Originality/Value: This study contributes to behavioral finance literature by integrating cognitive and social biases with internal locus of control as a moderator in an emerging market context.